STRATEGI ETHIOPIA DALAM MENGHADAPI MESIR TERKAIT DOMINASI HYDROENERGY DI KAWASAN SUNGAI NIL - Diya Meiliza Putri; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes Ethiopia's strategy in dealing with Egypt regarding hydroenergy in the Nile River Region. Egypt's hegemony on the Nile has made the construction of hydraulic construction in the Nile region of Ethiopia impossible. In an effort to secure hydro, Ethiopia launched the Grand Ethiopia Renaissance Dam (GERD) construction strategy to increase its national energy. This development is based on the increasing population in Ethiopia which requires greater use of energy apart from the essential role of the Nile for the people of Ethiopia. In launching its strategy, Ethiopia uses a normative mechanism through trilateral negotiations with Egypt and Sudan. The use of Ethiopia's bargaining power is increasing through opposition to the legitimacy of Egypt's status-quo in regional level negotiation forums, such as the Nile Basin Initiative (NBI). This strategy is not only useful for securing national water but also creates a hegemon shift scenario in the Nile River area. This research uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, websites. This research uses Realism perspective and Hydro-Hegemony theory. In explaining hydrohegemon, there are four pillars that are used to explain the domination of a country over other countries, namely Geographical power, Material power, Bargaining power, and Ideational power. The results of this paper indicate that the normative mechanism used for the development of GERD has been successful with the trilateral agreement reached with Egypt and Sudan. However, to replace Egypt's position as hegemon, Ethiopia needs to develop its bargaining power once its hydraulic project is completed. Keywords: Nile River, Water Securitization, Hydro-Hegemony Hydroenergy Domination, Grand Ethiopia Renaissance Dam